Options for improving effectiveness of rotavirus vaccines in developing countries. Issue 4 (3rd April 2017) - Tissera, Marion S.; Cowley, Daniel; Bogdanovic-Sakran, Nada; Hutton, Melanie L.; Lyras, Dena; Kirkwood, Carl D.; Buttery, Jim P.
ABSTRACT: Rotavirus gastroenteritis is a leading global cause of mortality and morbidity in young children due to diarrhea and dehydration. Over 85% of deaths occur in developing countries. In industrialised countries, 2 live oral rotavirus vaccines licensed in 2006 quickly demonstrated high effectiveness, dramatically reducing severe rotavirus gastroenteritis admissions in many settings by more than 90%. In contrast, the same vaccines reduced severe rotavirus gastroenteritis by only 30–60% in developing countries, but have been proven life-saving. Bridging this "efficacy gap" offers the possibility to save many more lives of children under the age of 5. The reduced efficacy of rotavirus vaccines in developing settings may be related to differences in transmission dynamics, as well as host luminal, mucosal and immune factors. This review will examine strategies currently under study to target the issue of reduced efficacy and effectiveness of oral rotavirus vaccines in developing settings.